2017
DOI: 10.18203/2394-6040.ijcmph20174214
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of falls and its associated factors among elderly living in old folks home in Kuala Lumpur, Malaysia

Abstract: INTRODUCTIONThe aging population is a phenomenon observed quite frequently during our time. The phenomenon appears to affect many high-and middle-income countries, including Malaysia and poses a real challenge to their society and healthcare systems, especially with the remarkably increased in the burden of diseases suffered by the aging population nowadays. Aside from chronic diseases, falls are also attributable to the challenges that need to be tackled and managed, brought about by the aging population. Fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The prevalence of falls in the last 6 months prior to the survey was 28.9% ( n = 336), consistent with a study done in institutional settings in Kuala Lumpur, with 30% ( n = 50) prevalence ( 43 ) and 27.3% ( n = 516) with history of falls in Melaka ( 44 ). In another study conducted in Brazil, with 400 participants aged 60 years or older, the prevalence of falls was 35.3% ( 45 ).…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of falls in the last 6 months prior to the survey was 28.9% ( n = 336), consistent with a study done in institutional settings in Kuala Lumpur, with 30% ( n = 50) prevalence ( 43 ) and 27.3% ( n = 516) with history of falls in Melaka ( 44 ). In another study conducted in Brazil, with 400 participants aged 60 years or older, the prevalence of falls was 35.3% ( 45 ).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies reported that the prevalence of falls among OP was approximately 30% in England, Brazil, and Indonesia (Gale et al, 2018;Siqueira et al, 2011;Susilowati et al, 2020). In Malaysia, 24.3%-32.8% of OP residing in nursing homes (Ghazi et al, 2017;Hami et al, 2019;Kioh and Rashid, 2018) and 14.1%-19.7% community-dwelling OP had fallen (Alex et al, 2018;Hami et al, 2019;Ibrahim et al, 2017;Sahril et al, 2020). Fall-related injuries such as fractures, hematoma, and severe laceration are the main consequences of falls that can result in disability, activity limitation, and dependency (Berg and Cassells, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…This study found out there is significant prevalence of risk of falls. 12 fall represents one of the public health problems among elderly living in old folk home in Malaysia with 30% prevalence among respondents. Our study is in concurrence with this research as it also depicts the high risk of falls in elderly.…”
Section: Discussionmentioning
confidence: 99%